2010
DOI: 10.1111/j.1600-0609.2010.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia as an adverse effect of complementary and alternative medicines, herbal remedies, nutritional supplements, foods, and beverages*

Abstract: Reports of thrombocytopenia describing definite or probable evidence for an association of a complementary/alternative medicines, herbal remedies, nutritional supplements, foods, and beverages are rare. Whether the occurrence of thrombocytopenia with these substances is uncommon or unrecognized is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…A case report put forth by Cerulli et al discusses the potential pathogenic side effects of this supplemental drug. These side effects observed included renal failure, thrombocytopenia, liver toxicity, and hemolytic anemia [16,18]. Of special consideration to this specific case, is the fact that in the case presented by Cerulli et al the thrombocytopenia was not observed until months after the initial ingestion.…”
Section: Discussionmentioning
confidence: 75%
“…A case report put forth by Cerulli et al discusses the potential pathogenic side effects of this supplemental drug. These side effects observed included renal failure, thrombocytopenia, liver toxicity, and hemolytic anemia [16,18]. Of special consideration to this specific case, is the fact that in the case presented by Cerulli et al the thrombocytopenia was not observed until months after the initial ingestion.…”
Section: Discussionmentioning
confidence: 75%
“…Examples reported were associated with consumption of an African bean, 2 sesame seeds, 3 cranberry juice, 4 cow’s milk, and Jui (a Chinese herbal medicine). 5 To the best of our knowledge this is the first case in which a patient reported systemic symptoms and in which a platelet-reactive antibody specific for a substance present in the implicated food was identified. With these findings and the positive provocation test, our patient’s case met all criteria for establishing a causal association between exposure and thrombocytopenia: 5 exposure to walnuts resulted in acute thrombocytopenia that rapidly recovered to normal; and no other cause for thrombocytopenia was identified.…”
mentioning
confidence: 82%
“…5 To the best of our knowledge this is the first case in which a patient reported systemic symptoms and in which a platelet-reactive antibody specific for a substance present in the implicated food was identified. With these findings and the positive provocation test, our patient’s case met all criteria for establishing a causal association between exposure and thrombocytopenia: 5 exposure to walnuts resulted in acute thrombocytopenia that rapidly recovered to normal; and no other cause for thrombocytopenia was identified. The provocation test led to profound thrombocytopenia, systemic symptoms, and bleeding, albeit followed by rapid recovery.…”
mentioning
confidence: 82%
“…Royer et al . ( 2010 ) found that after taking oral chromium picolinate tablets for 4–5 months for losing weight, the patient developed acute thrombocytopenia. Platelet count and other abnormalities returned to normal by day 26 after stopping chromium tablets.…”
Section: Effect Of Cr (Vi) On Plateletsmentioning
confidence: 99%